Advancing Democratic Engagement in Indonesia's Treaty Ratification Process: Memajukan Keterlibatan Demokratis dalam Proses Ratifikasi Perjanjian di Indonesia - Hamdani, Fathul; Asmara, M. Galang; Zunnuraeni (Universitas Muhammadiyah Sidoarjo, 2023)
This study explores the application of the 'meaningful participation' principle in the formation of laws ratifying international agreements in Indonesia, with a focus on social, economic, and environmental sectors. The research adopts a normative legal methodology, utilizing statutory and conceptual approaches to analyze relevant legislation, court decisions, and academic literature. The findings reveal a significant imbalance in public participation in the ratification process, primarily characterized by a top-down approach with minimal substantive dialogue with affected community groups. Despite constitutional provisions allowing the President to establish agreements without ratification, meaningful public participation in legislative and ratification processes remains limited. The study emphasizes the need for open public consultations, active involvement of non-governmental organizations, and private sector engagement to achieve policies that reflect the comprehensive interests and aspirations of the populace. It highlights the importance of community involvement, transparency, economic-environmental balance, and inclusive approaches in influencing meaningful participation levels. The research calls for recommendations to the Government and Parliament to foster more qualitative and significant public participation in the ratification process, aligning Indonesia with international principles of meaningful participation in social, economic, and environmental law. This approach is crucial for Indonesia, as the world's third-largest democracy, to promote meaningful public participation in policy-making, especially in ratifying international agreements impacting the broader society. Highlights: Imbalanced Participation: Dominance of a top-down approach with minimal public dialogue in treaty ratification. NGOs and Private Sector: Essential roles in representing diverse societal interests in legislative processes. Legal and Democratic Alignment: Need for transparent and inclusive law-making, balancing economic and environmental aspects. Keywords: Meaningful Participation, International Treaty Ratification, Public Involvement, Legislative Process, Indonesian Democracy